2012
DOI: 10.1159/000336077
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness Is Independently Related to Blood Leptin Concentration and Insulin Sensitivity Index in Male Subjects with Central Adiposity

Abstract: Aim: To compare the maximal power output (MPO) of subjects presenting a central adiposity to those of controls and to study the links between plasma leptin or indices of insulin sensitivity (QUICKI) and physical fitness (PF). Methods: MPO was determined for 169 middle-aged men divided into two groups according to waist circumference (WC– < 94 cm, WC+ ≧ 94 cm) each subdivided in two subgroups with low and high PF (WC-L, WC-H, WC+L, WC+H) determined from the median MPO relative to fat free mass (3.06 W/kgFF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 95 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Among the 19 studies ( Table 1 ), 18 applied training intervention [ 32 45 , 47 50 ], one compared the leptin levels of a mildly obese sedentary and a physically active group with similar BMI [ 46 ]. Regarding training, 13 studies applied a single (10-week to 6-month) training period [ 32 , 35 , 36 , 39 , 40 45 , 48 50 ], while 5 studies applied a 2-phase, 12-18-month training with the first leptin test after the first 3 or 6 months [ 33 , 34 , 37 , 38 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 19 studies ( Table 1 ), 18 applied training intervention [ 32 45 , 47 50 ], one compared the leptin levels of a mildly obese sedentary and a physically active group with similar BMI [ 46 ]. Regarding training, 13 studies applied a single (10-week to 6-month) training period [ 32 , 35 , 36 , 39 , 40 45 , 48 50 ], while 5 studies applied a 2-phase, 12-18-month training with the first leptin test after the first 3 or 6 months [ 33 , 34 , 37 , 38 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding gender, 6 studies reported data of men [ 36 , 40 , 41 , 43 , 44 , 46 ], 5 reported data of women [ 32 , 35 , 37 , 38 , 50 ], the remaining 8 merged data of men and women [ 33 , 34 , 39 , 42 , 45 , 47 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Leptin stimulates fatty acid oxidation in skeletal muscles and inhibits fat storage while promoting intramuscular lipolysis [35, 36]. Nevertheless, despite this positive effect of leptin on muscle metabolism, epidemiologic studies demonstrate a negative association between leptin with muscle mass and function [13, 37]. This inconsistency is believed to result from leptin resistance that develops with high-fat feeding and obesity [38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the incremental test started at a speed determined, during a warm-period, to elicit ~70% of age-predicted HR max⁡ , and the speed remained constant throughout the test, while the grade was increased by 2% every 2 minutes. The test continued until the subject could no longer exercise because of exhaustion or until other conditions, such as ECG changes or development of symptoms, made it unsafe to continue [12, 13]. …”
Section: Methodsmentioning
confidence: 99%